2016
DOI: 10.1515/opag-2016-0020
|View full text |Cite
|
Sign up to set email alerts
|

The potential of hybrid potato for East-Africa

Abstract: Potato is an important staple crop in East Africa. Most of the seed tubers are propagated in informal systems, whereby the tubers become deteriorated and contaminated, resulting in low crop yields. Potato breeding has not resulted in significantly improved varieties that overcome these constraints. Recently, true potato hybrid breeding technology has been developed, whereby diploid hybrids are generated by crossing between homozygous inbred parent lines. The first series of experimental hybrids were pre-screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 6 publications
0
28
0
Order By: Relevance
“…The rapid development of diploid hybrid breeding is coupled with the prospects to cardinally shorten the duration of the breeding process and reduce the costs of producing and multiplying healthy clones (Lindhout et al, 2011(Lindhout et al, , 2018De Vries et al, 2016;Jansky et al, 2016), because most of potato pathogens are not transmitted with pollen or TPS. The onset of diploid hybrid breeding called for a need to study genetic bases of self-incompatibility (Phumichai et al, 2005) and inbreeding depression in potato (Zhang et al, 2019) in order to obtain inbred diploid lines, as well as to promote research on male sterility and CMS-Rf genetic systems, aimed at the development of effective interline hybridization techniques (Anisimova, Gavrilenko, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The rapid development of diploid hybrid breeding is coupled with the prospects to cardinally shorten the duration of the breeding process and reduce the costs of producing and multiplying healthy clones (Lindhout et al, 2011(Lindhout et al, , 2018De Vries et al, 2016;Jansky et al, 2016), because most of potato pathogens are not transmitted with pollen or TPS. The onset of diploid hybrid breeding called for a need to study genetic bases of self-incompatibility (Phumichai et al, 2005) and inbreeding depression in potato (Zhang et al, 2019) in order to obtain inbred diploid lines, as well as to promote research on male sterility and CMS-Rf genetic systems, aimed at the development of effective interline hybridization techniques (Anisimova, Gavrilenko, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Solynta (a private company) has developed a true hybrid breeding system in diploid potato whereby homozygous parent lines are developed by several rounds of inbreeding and hybrid cultivars are generated by crossing these parent lines (Lindhout et al, 2011); the resulting true potato seeds were sown in seed boxes and later seedlings were transferred in the field. From their initial trial, the seedlings gave a maximum yield of 26 ton/ha and 29 ton/ha in Netherlands and DR Congo respectively (de Vries et al, 2016). However, these yields are far below the world average which stands at approximately 40 ton/ha (CSO, 2016); this is despite the intense care given to the delicate seedlings in this trial.…”
Section: Production Of Hybrid Potato Seedsmentioning
confidence: 87%
“…Previous studies have shown that seedling transplants produce lower tuber yields (ton/ha) and percentage of waresized tubers than a crop propagated from conventional tubers (Almekinders et al, 2009;Muthoni et al, 2014). The low yields reported in this trial could be due to three confounded factors: diploid versus tetraploid, experimental hybrid versus commercial cultivar and seedlings versus seed tubers (de Vries et al, 2016). Further tests with plants grown from convetional tubers and tetraploid experimental hybrids are needed to dissect these factors.…”
Section: Production Of Hybrid Potato Seedsmentioning
confidence: 92%
“…To obtain more homozygous, self-compatible diploid lines, Solynta ( www.solynta.com ) is setting up a mature breeding program with a selection of the best individuals in 750–1000 crossing diploid combinations every year and picking the best combinations to use as parents for selfings or crosses with other good parental lines. The first hybrid field trials have shown that diploid F1-hybrid breeding is making significant progress (De Vries et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%